Strategy formulation of ip radio product at fr telco facing hypercompetitive business environment in asia pacific - Magdalena Fenny P, Maria; Toha, Mohammad (The Indonesian Journal of Business Administration, 2016)
Abstract - FR Telco is a telecommunication device supplier based in France. Currently FR Telco face a very tight competition in the industry, particularly with supplier from China. For IP Radio product, specifically in Asia, FR Telco inability to compete due to premium price of FR Telco equipment compared to market price and long delivery lead time. To solve this problem, FR Telco has taken several steps. One of it is by having an integration with other supplier. This is done in order to leverage product portfolio of both companies to offer a flexibility in difining the strategy. In addition to that, the integration will strengthen FR Telco financial statement to acquire other suppliers to expand its technology portfolio. Proposed solution to resolve delivery lead time issue is through centroid methodology. With this methodology FR Telco will be able to locate the right location for manufacture and distribution center for Asia market. Thus, FR Telco will be able to optimize transportation cost and expedite delivery time. This recommended solution is expected can disrupt the high intense competition by providing more competitive price and increase speed of delivery product of FR Telco.Â Keywords : Â competition, low price, delivery time, disrupt the competition